Tegel och klinker : keramiska material på mark - Wieslander, Emilie (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
Being an architect I create spaces with roof, walls and fl oor. The availability of the essential materials to create such spaces is practically unlimited. The materials also play a significant part to the character of the created space. I hope to contribute to the general understanding of materials as elements in the design of urban spaces by having intensely explored one specific material in depth, pointing out its bad and good qualities. I am of the opinion that the reason for choosing a material shouldn't be because of a shortage of knowledge, facts or references, but what character you want for the room. When travelling across Europe, it sometimes feels like clay paving is everywhere, but back in Sweden it is almost unseen of in modern landscape architecture. I believe the lack of domestic producers is the main reason; one does not know whom to address. This creates a negative trend, no demand due to no marketing, and no marketing due to no demands. Clay in architecture started out as sun dried clay, adobe, and still today more than one third of the world's population lives in houses of sun dried clay. Eventually man discovered that the strength of the material was improved by burning it. As early as 6500bc, in present Iraq, a kind of burned clay was present. Ever since the beginning one has searched for ways of improvement and decoration. The first discoveries of glazed ceramic tiles go back to 3000bc, and the main street of early Babylon was brick paved. During the medieval time northern Europe also took up the use of ceramic materials in large scale. From the 17th century brick could be found on the streets of many northern European cities. To Sweden the use of bricks came along with the monks during the 12th century, in the building of monasteries. During the farm rationalization of the 19th century the major manors could afford to develop their private brickworks to permanent industrial brickworks. Also the introduction of the railway helped the spreading of the use of bricks. It was during this period clinkers came to Sweden, mostly for use in decorated floors in stairwells and gateways, but also outside on pavements. From the beginning of the 20th century and up until the 1950s clinker was used rather frequently in many of the cities of western Skåne. In many places clinkers from this period still remains today. Generally, in my opinion, buildings are seen as the principal upholders of cultural environments –such a simple thing as paving is not considered as important. I have never been in favour of preserving things for the sake of the preservation itself, but I think that the paving materials form a vital part of urban spaces. Even more so with old paving materials in old environments. The production of all ceramic materials consists of five main operations; 1. Mining of the clay, 2. Working and blending of the clay, 3. Moulding the products, 4. Drying the products, 5. Burning the products. The raw material in all ceramic production is clay, and the composition of the clay determines many of the qualities of the final product, for example it's colour. The colour is also affected by the temperature of the burning and the supply or absence of oxygen in the burning process. All materials have their weaknesses, but by creating best possible opportunities one can aid the material. For all production of clay pavers there is a European standard, EN1344, controlling frost resistance and strength among other things. The main problem in the use of clay pavers is that they have a tendency to get slippery when wet, or from frost or ice. By a well drained build up this can be prevented. And it is crucial to make sure that there is a fall when setting out the levels that will keep off the water from the surface. Another crucial thing are the joints. A joint of five mm is recommended for most clay pavings, if less one risks the pavers to splinter against one another. Ultimately I hope that designers of outdoor environments will start considering the ceramic materials and their possibilities. We should, even in new and modern designs, dare to experiment more with clay pavers and other materials on the ground. The technical limitations of clay pavers are not as severe as many people think, and in the long term it is a very satisfactory choice, economically, environmentally and aesthetically.